Factors Affecting the Stability of Operation of Industrial Facilities in Emergency Situations - Mahkamov Khusniddin; Norboev Abduahat; Shonazarov Otobek; Sharipov Javokhir (Zien Journals, 2022)
Under the stability of the object is understood its ability to perform the specified functions not only in normal, but also in emergency situations, to prevent the occurrence of accidents and disasters at the facility. In particular, production facilities must produce products in the required volume, range, specified quality and cost, ensuring competitiveness in the market.
Keywords: processes; situations; environment; territory